Formulation and Optimization of Bisoprolol Fumarate Orally Fast Dissolving Film with Combination of HPMC E15 and Maltodextrin as Matrix Polymers - Aristha Novyra Putri; Rahmayanti Fitriah (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Bisoprolol fumarate is a drug belonging β blockers group, and specifically is selective β1 adrenergic receptor blocker, a class medicines used primarily in cardiovascular diseases. The drug has 9-12 hrs half life (t1/2) and shows bioavailability of more than 80%1. An orally fast dissolving film dosage form with drug in mouth are absorbed through buccal/oral mucosa in to systemic circulation avoiding first pass metabolism2. The study aimed to made of orally fast dissolving film bisoprolol fumarate by solvent casting method with combination of HPMC E15 and maltodextrin as matrix. Factorial design 23was applied to optimize the formula of orally fast dissolving film bisoprolol fumarate by varying level of polymer, it was HPMC E15 300 – 600 mg, maltodextrin 50 – 150 mg, and PEG400 50 – 90 mg. The optimum formula was determined by superimposed contour plot from various parameters: physical properties of orally fast dissolving film bisoprolol fumarate such as thickness, folding endurance, surface pH, in vitro disintegration, hidration study, and drug release for 300 second using Design Expert ® program. The study result showed that physical properties of 8 formulas such as organoleptic test were transparent, homogeny, and smooth in both of side; thickness 0.062 – 0.132 mm; weight variation 50.85 – 70.60 mg; folding endurance 987 – 2012; surface pH 6.69 – 6.99; disintegration (drop method) 18.33 – 20.76 sec; disintegration (petridish method) 27.63 – 30.41 sec; in vitro dissolution for 300 sec was 94.35 – 98.99%; and swelling index up to 30 second was 146.63 – 173.34%. Based on superimposed contour plot Design Expert® from factor response of folding endurance, surface pH, in vitro disintegration drop method, in vitro disintegration petridish method, swelling index, dan DE300with a statistically significant finding requires a P-value of 0.05 were obtained optimum formulas for the area in the range of HPMC E15 509.88 mg; Maltodextrin 108.63 mg; and PEG400 50 mg with the value of desirability 0.519.Key Words: bisoprolol fumarate, orally fast dissolving film, factorial design